New records of the kodkod (Leopardus guigna tigrillo) and the Pampas cat (Leopardus colocola) in Valparaíso region, Chile - Guzmán Marín , Byron Cristian; Hernández-Hernández, Julio C.; Olmos de Aguilera-Díaz, Natividad (Therya Notes, 2022)
The kodkod, Leopardus guigna tigrillo and the Pampas cat, Leopardus colocola are two of the most elusive and cryptic species of wild cats in the Neotropical region. The few existing studies for both species suggested that their distribution is restricted almost entirely to large areas of native forest. Both species are classified within some category of extinction risk. As part of the citizen science projects, new records were obtained from the kodkod and the pampas cat in the central zone of Chile. In addition, to corroborate these records, previous records of both species were consulted in the available literature and databases. The site where the kodkod was sighted is an urban and beach area, with small strips of scrub, secondary native forest and forest plantations. The records of the Pampas cat were presented on roads, putting his integrity at risk. The records of both species were presented in sites with threats, where it is possible that due to the fragmentation of their habitats, they are forced to move to look for food resources where they did not before. Likewise, we highlight the importance of the vegetation fragments as biological corridors for these and other species that require large areas of continuous habitat, which is why it is necessary to prioritize the conservation of these sites in the region. It is essential to carry out more research in the region to know both species threats and population density.